Pilas de arena sobre grafos dirigidos y algo de complejidad (2006)
In this work we study the Abelian Sandpile Model on directed graphs. The model is more complex on directed graphs than on undirected graphs, because of which there are many questions that remain without an answer. We survey the basic theory of the model on directed graphs and present some new results.